Hukum Keluarga Berencana (KB) dalam Islam: Tinjauan Syar'i dan Pertimbangan Maslahat. - Adib Nabil Dwiananda; Annisa Qotrunnada; Dhefita Yuliana Putri; Exsa Rani Fadillah; Febri Nurul Aini (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2025)
This study critically examines the legal status of Family Planning (FP) within contemporary Islamic jurisprudence by articulating a clear doctrinal distinction between tanzhīm al-nasl (temporary birth regulation) and tahdīd al-nasl (permanent limitation of offspring). The inquiry responds to the rapid advancement of modern contraceptive technologies, which generate juridical questions insufficiently addressed in classical fiqh discussions largely confined to ‘azl (coitus interruptus). Situated within the normative tension between the prophetic encouragement to increase progeny and the imperative to ensure family welfare, this research argues for a maqāṣid-oriented ijtihād that safeguards the higher objectives of Sharī‘ah—particularly the protection of lineage (ḥifẓ al-nasl)—while engaging contemporary socio-medical realities. Employing a qualitative library-based methodology with a descriptive-analytical and comparative fiqh approach, the study draws upon primary sources from the Qur’an and Hadith, as well as authoritative fatwas issued by institutions such as the Indonesian Council of Ulama (MUI) and the International Islamic Fiqh Academy. Data are examined through content analysis to evaluate textual evidence, identify operative legal causes (‘illah), and perform tarjīḥ to determine the most contextually sound ruling. The findings demonstrate that temporary birth regulation is legally permissible (mubāḥ) when grounded in mutual spousal consent and considerations of maṣlaḥah mursalah, particularly maternal health and child welfare. Conversely, permanent sterilization is presumptively prohibited (ḥarām) due to its contradiction with ḥifẓ al-nasl, except in cases of compelling medical necessity that threaten the mother’s life and are substantiated by professional medical judgment.